Paul : his life and teaching - McRay, John. (Grand Rapids, MI, Baker Academic, 2003)
""I have tried to emphasize that Paul was not the founder of Christianity, that he never ceased to be a Jew, and that Christianity is not a Gentile religion. There has never been a greater advocate of the universal composition of the Christian faith than Paul... When people place their trust in Jesus, neither Jews nor Gentiles have to abandon their ancestry, neither males nor females have to abandon their gender, and neither slaves nor free people have to abandon their sociological status. Paul's central focus in his preaching was that Gentiles do not have to become Jews any more than Jews have to become Gentiles... Wherever God has a son or daughter, I have a brother or sister (Jew or Gentile, male or female). The impact of this truth can be nothing short of revolutionary in a world filled with religious division, if the teaching of Paul is accepted and applied with love to everyday life."" ""It has been my aim to produce a volume that essentially reflects the content and method of my college courses on Paul and the results of my twenty-seven trips to the Holy Lands studying Paul's world. As I exhort my students to do, I have tried to 'put on my first-century glasses' and look at Paul in his Jewish and Hellenistic world of the Mediterranean and see him not as a fourth-century church father, a sixteenth-century Protestant reformer, or a twenty-first-century evangelical missionary, but as what he was, a first-century Jewish rabbi who accepted Jesus as his Messiah and became an ardent, dedicated Messianic Jew." Book jacket."--BOOK JACKET.
pt. 1. Paul's life. Background and biography ; Conversion, call, and commission ; Toward a chronology of Paul's ministry ; In Syria, Arabia, and Cilicia before the first journey ; Paul's first journey ; Paul's second journey ; Paul's third journey ; The voyage to Rome, later travels, and death -- pt. 2. Paul's teaching. The form, function, and canonicity of Pauline letters ; Paul's world of apocalyptic and demonology ; Paul and the incarnation of Jesus Christ ; Atonement in Pauline literature ; The heart of Paul : the theology of Ephesians ; The faith(fulness) of Christ in Pauline literature ; Paul's view of the law ; The composition of Paul's churches : organization, Lord's Supper, and baptism ; Eschatology and the work of the Holy Spirit in Paul's thought ; Paul in recent study.
Includes bibliographical references and indexes.
Keywords: Paul, -- the Apostle, Saint